TEACHER’S COGNITIVE AND AFFECTIVE VERSUS TEACHERS’ WRITING ASSESSMENT - Endang Mastuti Rahayu; Endah Yulia Rahayu (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2019)
Many English teachers are not confident when they are required to examine their students essay although they have sufficient education and experience in assessing their students’ written works. Therefore, they need to be trained over a short period to rate their students’ writing. They are also required to improve their knowledge or cognitive in order to literate ESL writing assessment to focus their students on learning to write and to edit their writing. Their affective or attitude to the feedback of writing assessment for writing instruction, the importance of writing assessment, the competence to administer the assessment, time-consuming writing assessment, the confidence of good writing instructor affect their quality in writing assessment. Therefore, in real practice of assessing writing, experienced teachers mostly plan and do their assessment based on what they believe about the assessment. Thus, successful assessing students’ writing does not only constitute the major portion of second language writing teachers’ workloads but also quantifies teachers affective factors. In addition, in administering assessments, teachers as raters need to care their students' and their own affectiveness, so students will value what they learn and teachers will pay attention more to their students’ learning.